Species of Russula subgenus Heterophyllidiae (Russulaceae, Basidiomycota) from Dinghushan Biosphere Reserve - Song, Yu (European Journal of Taxonomy, 2022)
Two new species of subgenus Heterophyllidiae subsection Cyanoxanthinae, Russula fusiformata Y.Song sp. nov. and R. purpureorosea Y.Song sp. nov., collected from the Dinghushan Biosphere Reserve (DHSBR), are described based on both morphology and a phylogenetic analysis of the internal transcribed spacer (ITS), further increasing Heterophyllidiae species diversity in the area. Differences between the two new species and related taxa are analyzed. The other 17 reported species of Russula subgenus Heterophyllidiae that have been collected from DHSBR during mushroom explorations since 2014 are also summarized. The dominant species and the ecological distribution of all 19 species are briefly discussed, and most species are presented in macrofungal plates.